The Effect of Service Quality and Perception of Financing Margins on Financing Decisions and Its Impact on Customer Satisfaction - Vironica Nurani Yonatan; Mohamad Rizan; Saparuddin Mukhtar (LPPM Universitas Negeri Jakarta, 2020)
The rise of digitalization of financial services has led to the emergence of many fintech (financial techology) start-ups. However, because fintech startups have several risks, the Bank remains the main option in selecting financing / credit service products for bankable people. This research was conducted at PT Bank Syariah Mandiri with a purposive sampling method. The data was collected by distributing questionnaires using a Likert scale. The analysis technique used is Structural Equation Modeling (SEM) to calculate the effect of each variable. The results of the study reveal that service quality has a positive and significant effect on the decision to request financing, the perception of the margin of financing has a positive and significant effect on the decision on financing application, the quality of service has no positive and insignificant effect on customer satisfaction, the perception of the size of the financing margin has a positive and significant effect on satisfaction. Customer, the decision to request financing has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer satisfaction, which is mediated by the decision on a financing request, the perception of the size of the financing margin has a positive and significant effect on the variable of customer satisfaction, which is mediated by the variable of financing request decision. Based on the result, banking services can increase financing margins that this is can relate with customer purchasing decision.